Abu Raihan al-Biruni's Thoughts about Hisab Rukyah - Abdul Kohar (Al-Mizan (e-Journal), 2018)
Abu Raihan al-Biruni is a Muslim scientist who was popular during the Abbasid dynasty. His famous monumental work is Al-Qanun Al-Masudi. This article discusses the calculation of the various positions of celestial bodies and also discusses various phenomena of celestial bodies related to the time of worship of Muslims. One of al-Biruni's biggest contributions in the field of reckoning is completing the calculation of the Qibla Direction accurately based on the rules of the spherical triangle. This discovery which caused al-Biruni to be called the inventor of spherical trigonometry. In the field of hisab rukyah al-Biruni also explained the characteristics of eclipses and the criteria for the beginning of the Moon, including the height of the sun when entering time and dawn. Al-Biruni's other contribution was to succeed in calculating the movements of the Sun and the Moon such as the length of the tropical year, the movement of the sun in Apoge, daily Anomalies and the average of the Moon, the distance of the Earth-Moon and others. Data obtained by al-Biruni is not much different from modern data at this time.